2002
DOI: 10.1002/ana.10323
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term amygdalohippocampal stimulation for refractory temporal lobe epilepsy

Abstract: Short-term deep brain stimulation (DBS) recently has been shown to be efficacious in refractory temporal lobe epilepsy. We (1) evaluated long-term DBS in medial temporal lobe structures in patients with normal magnetic resonance imaging (MRI) findings and (2) investigated the use of chronic DBS electrodes for the localization of the ictal onset zone before DBS. In three patients with complex partial seizures (CPSs), DBS electrodes were implanted in the amygdalohippocampal region to identify and subsequently st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
177
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(195 citation statements)
references
References 20 publications
(21 reference statements)
10
177
1
6
Order By: Relevance
“…Recent studies have shown that brain stimulators placed within an epileptogenic zone in an attempt to control temporal focal seizures can reduce the occurrence of epileptiform discharges (Vonck et al, 2002;Yamamoto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that brain stimulators placed within an epileptogenic zone in an attempt to control temporal focal seizures can reduce the occurrence of epileptiform discharges (Vonck et al, 2002;Yamamoto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, several attempts have been made to use deep-brain electrical (Velasco et al, 2000a(Velasco et al, ,b, 2001Vonck et al, 2002;Yamamoto et al, 2002) or transcranial magnetic stimulation (Menkes and Gruenthal, 2000;Tergau et al, 1999) to abate seizures in patients presenting with epileptic disorders resistant to antiepileptic drugs, including mesial temporal lobe epilepsy (MTLE). These stimulating procedures have been often proved to be effective in reducing and/or abolishing both interictal and ictal discharges.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of neuromodulation on deep brain nuclei 4,10,12,20,[36][37][38]43 exerts seizure control by anterograde or antidromic stimulation or inhibition of the cortex, 21 but no conclusive data on the ideal parameters for stimulation are known. The experience reported by Kahane et al 17 demonstrated seizure induction with frequency parameters ranging between 1 and 50 Hz.…”
Section: Discussionmentioning
confidence: 99%